Joiking life narratives. The performance of indigenous self-perception in Sami life stories - Nicola Renzi (University of Bologna, 2021)
The Sami are the only indigenous population formally recognized in the EU, nevertheless, this significant acknowledgment came only in relatively recent times, after centuries of forced assimilation policies and thanks to crucial fights for self-determination and identity recognition. This article intends to offer an analysis of two cases of Sami life narratives orally transmitted as joiks, musical expressions traditionally sung a cappella and characterized by a highly descriptive value. The focus is to present, through a set of transdisciplinary approaches, intimate and social perceptions of indigeneity and the related narrative outcomes which may take place in the peculiar empathic relationship established between the narrator-performer and the audience. Lawra Somby’s Im manne gåarkah and Niiles-Jouni Aikio’s Ieš joiks will respectively direct the study through 1) the author’s individual life experience and perception of the colonial assimilation and the consequent language loss and 2) a rare case of self-joiking, an acoustic self-portrait or musical autobiography which through both verbal and musical components aims at the narration and interpretation of a Sami’s own life experience.